2022
DOI: 10.12688/f1000research.27744.3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional assessment of cardiovascular risk factors in patients with knee osteoarthritis

Abstract: Background: Osteoarthritis (OA) and cardiovascular disease (CVD) are prevalent in India. However, there is dearth of literature among Indians studying the relationship between the two. This study was carried out to assess various cardiovascular (CV) risk factors in patients with knee OA with an objective to investigate their association, screening and management.  Methods: In total, 225 patients were included in this cross-sectional study. Participants were diagnosed with knee OA on the basis of the Kellgren a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“… 6 , 7 Grade-4 knee OA patients had higher frequency of cardiovascular risk factors (p<0.05) and less life expectancy then Grade-2. 2 Chinese and Pakistani studies has shown increased prevalence of metabolic syndrome that (58.9%) in OA patients. 8 Research suggests key roles of meta-inflammation, (adipokines-leptin) in OA, metabolic syndrome and CVD, the role of adiponectin remains controversial in both CVD and OA as it may exert pro-inflammatory and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“… 6 , 7 Grade-4 knee OA patients had higher frequency of cardiovascular risk factors (p<0.05) and less life expectancy then Grade-2. 2 Chinese and Pakistani studies has shown increased prevalence of metabolic syndrome that (58.9%) in OA patients. 8 Research suggests key roles of meta-inflammation, (adipokines-leptin) in OA, metabolic syndrome and CVD, the role of adiponectin remains controversial in both CVD and OA as it may exert pro-inflammatory and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 96%
“…Worldwide prevalence is around 3.5%, occurs in old age and its increasing in developed and developing countries, very important public health problem. 1,2 The prevalence ranges from 12.3% to 21.6% in France and USA, more in women than men, common in developed than developing countries. 1 According to the COPCORD study In Iran's, rural population the prevalence was high (19.3%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation